The effect of ESG performance on open innovation: Evidence from China - Li, Qiong; Sawandi, Norfaiezah; Hashim, Mohd Farid Asraf Md (Asian Journal of Economic Modelling, 2025)
This study aims to explore the link between corporate Environmental, Social, and Governance (ESG) performance and the practices of open innovation within firms, as well as investigating the underlying mechanisms. It employs data from China's A-share listed companies spanning the period 2018–2023, comprising a final sample of 17,250 firm-year observations. This research relies primarily on fixed-effects OLS regressions for model estimation. The results reveal that stronger ESG performance significantly enhances corporate open innovation. Concurrently, that ESG performance promotes open innovation is partly mediated by alleviating financing constraints. Further investigation indicates that each dimension of ESG independently enhances open innovation capability, with financing constraints also mediating these individual linkages. These findings bear important implications for economic modeling: first, by internalizing ESG as a non-financial factor, they enrich theoretical models of corporate innovation decisions; second, by developing a resource-channel model with financing constraints as the core mediator, they strengthen the explanatory power of the green–innovation linkage. Accordingly, policy efforts should focus on integrating ESG criteria into national open innovation incentives, developing ESG-linked financial instruments to lower capital costs, and establishing mandatory ESG disclosure. These measures aim to fully harness ESG's direct and indirect benefits for open innovation.